(untitled) (Sains Humanika, 2023)
Stress is a normal occurrence in human lives, and university students can never escape from experiencing stress at least once during their university years, during which they have to face a variety of stressors. Poor sleep quality happens to people of all ages worldwide, particularly university students. Numerous studies have reported that stress significantly correlates with sleep quality among university students from various courses. However, these variables were less explored by past researchers, specifically on engineering students. In order to explore more information on these variables among engineering university students, a cross-sectional, quantitative, correlational study is conducted to identify the relationship between stress and sleep quality among engineering students in Malaysia. A total of 272 undergraduate engineering students from three public universities in Malaysia were involved in the study. The Perceived Stress Scale (PSS-10) and Pittsburgh Sleep Quality Index (PSQI) were used. The result from the correlational analysis shows that there is a significant negative relationship between stress and sleep quality among engineering students. The study’s findings could be used as a reference for future studies and recommend interventions to improve students’ stress and sleep quality levels.